The identification of facilities management standard service category for industry / Zuraihana Ahmad Zawawi ... [et al.] - Zuraihana, Ahmad Zawawi; Wan Samsulzamani, Wan Hamdan; Azfahani, Ahmad; Nurul Fadzila, Zahari (Universiti Teknologi MARA, Perak, 2016)
In Facilities Management (FM) industry, there are demands for different standards of service ranging from superior to basic for similar service provision. The establishment of the standard service category is essential to provide guidance and a framework for the development of the scope of service. However, the standard service category for FM service provider in Malaysia has not been established yet. Thus, this paper is aimed to propose a FM standard service category to be as guidance in Malaysia FM industry. The identification of the appropriate standard service category is the key to the success of FM services delivery